A Study of Sick Newborn for Inborn Error of Metabolism by Tandem Mass Spectrometry. Issue 2 (June 2022) - Bhautara, Rahul; Agarwal, Kamlesh Kumar; Gupta, Ashok; Goyal, Manisha; Kapoor, Seema
Introduction: Inborn errors of metabolism (IEM) form a large class of genetic diseases involving congenital disorders of metabolism. In most disorders, problems arise due to the accumulation of various toxic substances. Although some IEMs are harmless (benign), many can cause significant handicaps. Screening for IEMs among newborns not only prevents premature death and permanent neurological damage but also helps in planning prenatal diagnosis in future pregnancies. Tandem mass spectrometry (TMS) is an effective diagnostic technique and has been proposed as a means to realize this aim. Therefore, this study was planned to screen the sick newborns for inborn error of metabolism by TMS and to diagnose IEM as early as possible to minimize morbidity and mortality in sick/high-risk neonates. Material and Methods: This hospital-based descriptive diagnostic study was conducted in the Department of Pediatrics, SPMCHI, SMS Medical College, Jaipur from June 2017 to May 2018. The study population included indoor 90 patients with age up to 28 days of life who were enrolled after applying exclusion criteria. All data were collected and analyzed with the help of suitable statistical parameters. Results: Out of 90 cases enrolled, 66 were of normal birth weight and 24 were of low-birth weight neonates and all positive subjects were low birth weight. Out of 90 neonates, 7 (7.8%) were positive for IEM and 83 (92.2%) were negative for IEM. Out of 7 positive, 3 (42.8%) had maple syrup urine disease, 2 (28.6%) had methylmalonic acidemia and 2 (28.6%) had carnitine palmitoyl transferase type 1 deficiency/mitochondrial myopathy. Out of 90, 26 (28.9%) were positive and 64 (71.1%) were negative for hypoglycemia. Out of 7 cases of IEM, 6 (85.7%) were positive and 1 (14.3%) was negative for hypoglycemia. Conclusion: Screening helps in early diagnosis and initiation of treatment. Early treatment and rehabilitation to the child with IEM prevent premature death and permanent neurological disability.